Don't Lead Alone: Think Like a System, Act Like a Network, Lead Like a Movement! - and Justis, Cleveland; Student, Daniel (Fast Company Press, 2023)
Think. Act. Lead.It seems simple enough. But understanding your desired impact and how it fits into a larger picture, connecting your work to others and finding new collaborators, and bringing those collaborators together and moving them in a unified direction is never easy.Governments, businesses, and nonprofits all have unique approaches and ideas that many of us learn through our work. Yet, we rarely consider the skills needed to create and maintain the partnerships between them. Most of us learn those skills through trial, error, and often, failure. Worse, we typically stay in our self-reinforcing silos, sharing perspectives and frustrations with like-minded people, limiting our vision of what our work can become. By partnering with other sectors, we combine and adapt approaches to solve complex problems, and leaders in any industry can create large-scale change.Cleveland Justis and Daniel Student share a road map for effective partnerships that increase impact and profitability. Using real-life examples and practice exercises, the authors teach how to acquire and use skills to solve complex problems and propel your organization forward by combining a multitude of perspectives, split into three sections:Think Like a SystemAct Like a NetworkLead Like a MovementIt’s time to get out of our silos. Don’t lead alone.